Differences in Muscle Oxygenation, Perceived Fatigue and Recovery between Long-Track and Short-Track Speed Skating - Hettinga, Florentina J.; Konings, Marco J.; Cooper, Chris E. (Frontiers in Physiology, 2016)
Due to the technical nature of speed skating, that is affecting physiological mechanisms such as oxygenation and blood flow, this sport provides a unique setting allowing us to uncover novel mechanistic insights of the physiological response to exercise in elite middle-distance and endurance sports. The present study aimed to examine the influence of skating mode (short-track vs. long-track) on muscle oxygenation, perceived fatigue, and recovery in elite speed skating. Muscle oxygenation of twelve talented short-track speed skaters was continuously monitored during a long-track (LT) and a short-track (ST) skating time-trials of maximal effort using near-infrared spectroscopy (NIRS) on the m. vastus lateralis for both legs. Video captures were made of each testing session for further interpretation of the muscle oxygenation. To determine recovery, perceived exertion was measured two and four hours after each testing sessions. Repeated measures ANOVA’s were used for statistical analysis (p<.05). After a rapid desaturation in both legs directly after the start, an asymmetry in muscle oxygenation between both legs was found during LT (tissue saturation-index (TSI%)-slope: left=0.053±0.032; right=0.023±0.020, p<.05) and ST speed skating (TSI%-slope: left=0.050±0,052, right=0.001 ±0.053, p<.05). Re-Resaturation of the right leg was relatively lower in ST compared to LT. For the left leg, no difference was found between skating modes in muscle oxygenation. Respectively, two (ST=5.8±2.0; LT=4.2±1.5) and four hours (ST=4.6±1.9; LT=3.1±1.6) after the time-trials, a higher rate of perceived exertion was found for ST. Based on our results, ST seems more physiologically demanding, and longer periods of recovery are needed after training compared to LT. Technical aspects unique to the exercise mode seem to impact on oxygenation, affecting processes related to the regulation of exercise intensity such as fatigue and recovery.